The Effect of Earnings Management to Stock Return on Company Listed in Indonesia - Sukiantono Tang; Wini Alvita (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
The financial report should report accurate information about the company situation so it can be utilized properly by stakeholders. This study aims to examine the effect of earnings management on stock returns. The data collection of this study used purposive sampling. A total of 1335 data were collected and used as research samples. The data that has been collected is then tested to obtain the results. Furthermore, in analyzing the data, the method used is descriptive statistics. Based on the analysis, the results of this study showed that earnings management has a significant effect on the stock return variable. This is because earnings management practices can trick investors into making investment transactions.